Hypohidrotic ectodermal dysplasia with autosomal recessive inheritance pattern: Report of a rare and unusual case with a brief review of literature - Hasan, Shamimul (J Oral Maxillofac Pathol, 2019)
Ectodermal dysplasia (ED) is a congenital disorder primarily affecting the ectodermal tissue, with infrequent dysfunction of mesodermally derived tissues. Clinically, there are two major forms seen, hypohidrotic/Christ–Siemens–Touraine syndrome and hidrotic/Clouston syndrome, depending on the number and function of sweat glands. A multidisciplinary treatment protocol is usually followed and necessitates collective efforts by medical and dental professionals. Dental intervention should be done as early as possible to ameliorate the patient's esthetics and enhance the emotional and psychological quotient in these patients. This case report aims to highlight a rare and interesting report of hypohidrotic ED in a young female patient with a possible autosomal recessive inheritance pattern.